2011
DOI: 10.1177/1545109711418361
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension is Common among HIV-Infected Persons, But Not Associated with HAART

Abstract: Hypertension is common among HIV-infected persons and is associated with established risk factors, but not with HAART use. Given the high prevalence of hypertension and its association with duration of HIV infection, other factors such as virally-mediated endothelial changes or immune activation may play a role. Further investigations are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 27 publications
9
42
2
Order By: Relevance
“…The highest number of studies were from Norway 5,23,25,26 and United States of America. 6,8,29,36 The total mean age was 39.2 years (30 studies [n = 32 374 patients]), with patients in high-income countries being older than those in low-and middleincome settings (mean age = 40.4 versus 37.8 years). Among the ART-exposed patients, the overall mean duration of treatment was 37.5 months (23 studies (n = 36 423)).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The highest number of studies were from Norway 5,23,25,26 and United States of America. 6,8,29,36 The total mean age was 39.2 years (30 studies [n = 32 374 patients]), with patients in high-income countries being older than those in low-and middleincome settings (mean age = 40.4 versus 37.8 years). Among the ART-exposed patients, the overall mean duration of treatment was 37.5 months (23 studies (n = 36 423)).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 573 abstracts and 17 full texts, including seven duplicate records, were excluded, leaving 39 eligible observational studies. [5][6][7][8]15,16, Thirty of these included studies were cross-sectional surveys, 5,16,[18][19][20][21][22][23][24][25][26]28,[31][32][33][34][35][36][37][39][40][41][42][44][45][46]48,49 whereas the other nine were cohort studies. A total of 44 903 HIV-infected patients (28% females) from 21 countries were included in our analyses, with significantly more study participants from high-income countries compared with low-and middle-income countries (89% versus 11%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Muhammad et al (2013) reported a prevalence of 17% of hypertension cases in HIV patients mainly on NNRTI-based HAART during 6-84 months. In Western countries, many studies showed hypertension proportion among HIV patients on HAART ranging from 13% to 34% (Gazzaruso et al, 2003;Jung et al, 2004;Bergersen et al, 2003;Medina-Torne et al, 2012;Savès et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Hypertension is associated with established risk factors, and is common among HIV-infected individuals. The high prevalence of hypertension has been associated with duration of HIV infection, whereas virally-mediated endothelial changes or immune activations may play a role [20].…”
Section: Discussionmentioning
confidence: 99%